Fibroblast Growth Factor 23 and Long-Term Cardiac Function: The Multi-Ethnic Study of Atherosclerosis. (November 2020) - Patel, Ravi B.; Ning, Hongyan; de Boer, Ian H.; Kestenbaum, Bryan; Lima, João A.C.; Mehta, Rupal; Allen, Norrina B.; Shah, Sanjiv J.; Lloyd-Jones, Donald M.
Abstract : Background: Although FGF23 (fibroblast growth factor 23) is associated with heart failure and atrial fibrillation, the mechanisms driving these associations are unclear. Sensitive measures of cardiovascular structure and function may provide mechanistic insight behind the associations of FGF23 with various cardiovascular diseases. Methods: In MESA (the Multi-Ethnic Study of Atherosclerosis), we evaluated the associations of baseline serum FGF23 (2000–2002) with measures of left ventricular (LV) and left atrial mechanical function on cardiac magnetic resonance at 10-year follow-up (2010–2012). Results: Of 2276 participants with available FGF23 and cardiac magnetic resonance at 10-year follow-up, participants with higher FGF23 levels were more likely White race, taking antihypertensive medications, and had lower kidney function. After covariate adjustment, FGF23 was associated with higher LV mass (β coefficient per 1 SD higher, 1.14 [95% CI, 0.16–2.12], P =0.02), worse LV global circumferential strain (β coefficient per 1 SD higher, 0.15 [95% CI, 0.05–0.25], P =0.003), worse LV midwall circumferential strain (β coefficient per 1 SD higher, 0.20 [95% CI, 0.08–0.31], P =0.001), and lower left atrial total emptying fraction (β coefficient per 1 SD higher, −0.52 [95% CI, −1.02 to −0.02], P =0.04). These associations were consistent across racial/ethnic groups and the spectrum of glomerular filtration rates. FGF23 was not associated with the presence of myocardial scar (odds ratio per 1 SD higher, 1.12 [95% CI, 0.86–1.45], P =0.42). Conclusions: In a multiethnic, community-based cohort, baseline FGF23 levels were independently associated with higher LV mass, lower LV systolic function, and reduced left atrial function over long-term follow-up. These findings provide potential mechanistic insight into associations of FGF23 with incident heart failure and atrial fibrillation. Abstract : Supplemental Digital Content is available in the text.